Family practice web sites: new perspectives for patient care and health information? - Freund, Tobias; Freund, Michaela; Mahler, Cornelia; Schwantes, Ulrich; Ose, Dominik; Joos, Stefanie; Szecsenyi, Joachim (Family Medicine, 2010)
BACKGROUND AND OBJECTIVES: To cater to the needs of informed and proactive patients in family medicine, health care providers could offer access to care and health information via practice Web sites. To determine the content and quality of family medicine Web sites, we performed a cross-sectional study on a large sample of family practices' Web sites in Berlin, Germany. - METHODS: After screening of all family medicine practices in Berlin for the provision of their own practice Web site, we determined the content and quality using a predefined checklist based on a review of literature. - RESULTS: Among 1,453 family practices in Berlin, only 211 (15%) had an accessible Web site. Online tools for appointment scheduling (17/211, 8%) or prescription ordering (8/211, 4%) were rarely provided. Approximately half of all Web sites (102/211) provided health information on a wide range of topics, with complementary medicine dominating. Transparency about the source and currentness of information and barrier-free design were identified as main areas in which there was a need for quality improvement. - CONCLUSIONS: Family physicians should be trained in quality requirements for Web sites and in how to use online solutions for practice reorganization.
Gesehen am 19.12.2023